Comparison of the meat quality of Thai indigenous Upland Cattle and F2-crossbreds with 75% Charolais blood proportion - Chaiwang N. (Taylor and Francis Ltd., 2014)
The aim of the present study was to investigate the difference in meat quality between local Thai indigenous Upland Cattle (Bos indicus) and Charolais × generic Thai native cattle crossbreds (here: F2, 75% blood proportion of Charolais), an increasingly preferred option of farmers in Northern Thailand. Eight bulls of the F2-crossbred genotype and eight of the Upland Cattle genotype were fed ad libitum with grass and were supplemented with concentrate at 1.5% of body weight until they were on average 4 years old. In the Longissimus dorsi (LD) muscle, pH at 45 min and 24 h post-mortem as well as luminosity were lower and redness was higher in the F2-crossbreds than in the Upland Cattle. The beef of the F2-crossbreds also expressed lower drip, thawing and cooking losses. There was no difference in grilling loss. The LD of the F2-crossbreds contained less moisture and more protein, fat and cholesterol than that of the Upland Cattle, and was richer in total and soluble collagen. Still, the beef of the F2-crossbreds was scored as more tender and had a lower shear force. Additionally it was scored to have a higher intensity of beef flavour as well as off-flavour and an overall better acceptability. Overall this suggests that a clearly better meat quality can be achieved by the crossbreeding strategy, but this was associated with higher fat and cholesterol contents. Further studies have to show which part of the changes in meat quality resulted from the large differences in body size of the two genotypes. Consideration for or against crossbreeding have to include animal welfare and health aspects.